Cultivating Food Justice : Race, Class, and Sustainability - Alkon, Alison Hope; Agyeman, Julian (Food, health, and the environment., 2011)
Documents how racial and social inequalities are built into our food system, and how communities are creating environmentally sustainable and socially just alternatives.